LEGAL SYSTEM THEORY PERSPECTIVE ON CHILD MARRIAGE IN INDONESIA AFTER THE AMENDMENT TO THE MARRIAGE LAW - Purnomo, Agus; Rohmatulloh, Dawam Multazamy (Ulul Albab: Jurnal Studi Islam, 2022)
This article critically examines the ideality and effectiveness of Indonesia’s amended Marriage Law in curbing child marriage, a persistent socio-legal issue with deep-rooted cultural and religious dimensions. Despite legal reforms, child marriage continues to occur at alarming rates, raising questions about the law’s capacity to address structural and normative barriers. Employing Lawrence M. Friedman’s legal system theory, this study analyzes the problem through the interrelated dimensions of legal structure, legal culture, and legal substance. Methodologically, this research adopts a normative-empirical legal approach, integrating doctrinal legal analysis with socio-legal inquiry to assess the sources, functionality, and enforcement of relevant legal instruments. Findings reveal a critical tension between the amended law and prevailing cultural norms. In the dimension of legal culture, the entrenched influence of kitab kuning—traditional Islamic legal texts—continues to shape societal attitudes and justify early marriage, thereby weakening the law’s preventive potential. From the perspective of legal substance, the absence of explicit sanctions for violators constitutes a significant legal loophole, undermining the deterrent effect of the amendment. Nonetheless, in the dimension of legal structure, the issuance of Supreme Court Regulation No. 5 of 2019—governing judicial review of marriage dispensation cases—reflects a proactive institutional response aimed at restricting the practice. This study underscores the urgency of harmonizing legal reform with cultural transformation and institutional enforcement. Its contribution lies in highlighting the multi-dimensional challenges of legal ideality in child marriage prevention and offering a systemic framework for more effective policy implementation.